2008
DOI: 10.1074/jbc.m706001200
|View full text |Cite
|
Sign up to set email alerts
|

Mannose Inhibits Hyaluronan Synthesis by Down-regulation of the Cellular Pool of UDP-N-acetylhexosamines

Abstract: We found that D-mannose dose-dependently decreases hyaluronan synthesis in cultured epidermal keratinocytes to ϳ50%, whereas glucose, galactose, and fructose up to 20 mM concentration had no effect. The full inhibition occurred within 3 h following introduction of mannose and did not involve down-regulation of hyaluronan synthase (Has1-3) mRNA. Following introduction of mannose, there was an ϳ50% reduction in the cellular concentration of UDP-N-acetylhexosamines (UDPHexNAc, i.e. UDP-N-acetylglucosamine and UDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
60
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 54 publications
1
60
0
Order By: Relevance
“…Raising cellular UDP-GlcUA content stimulates hyaluronan synthesis, whereas a low concentration of UDP-GlcUA can limit the synthesis (12,17). We have shown that the same applies to UDP-GlcNAc: limiting or increasing its content stimulates and inhibits, respectively, the synthesis of hyaluronan (18).…”
mentioning
confidence: 73%
See 4 more Smart Citations
“…Raising cellular UDP-GlcUA content stimulates hyaluronan synthesis, whereas a low concentration of UDP-GlcUA can limit the synthesis (12,17). We have shown that the same applies to UDP-GlcNAc: limiting or increasing its content stimulates and inhibits, respectively, the synthesis of hyaluronan (18).…”
mentioning
confidence: 73%
“…2C). Notably, although mannose increased the content of UDPGlcUA, this could not prevent the decreased synthesis of hyaluronan caused by UDP-HexNAc depletion because equimolar amounts of each substrate are needed (18).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations